2020
DOI: 10.3389/fonc.2020.01751
|View full text |Cite
|
Sign up to set email alerts
|

HPV Detection in Head and Neck Squamous Cell Carcinomas: What Is the Issue?

Abstract: Besides classic tobacco and alcohol risk factors, human papillomavirus (HPV) plays a role in the development of a subset of head and neck squamous cell carcinomas (HNSCCs), and notably oropharynx squamous cell carcinomas (OPSCCs). HPV-induced OPSCCs have a different biological behavior and a better prognosis compared to non-HPV-induced OPSCCs and the eighth-edition TNM classification now separates these two entities. Therefore, determining the HPV status of patients with OPSCC is now essential for treatment, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
58
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 136 publications
(201 reference statements)
0
58
0
6
Order By: Relevance
“…Though the current standard methods for detection of HPV infection in OPSCC are based on detection of E6/E7 mRNA detection [ 33 ], OPSCC tumor samples were mainly obtained as FFPE tissue in which RNA might not be reliably preserved [ 34 36 ]. Therefore, in our study, we selected HPV DNA detection method by qPCR to confirm the presence of HPV infection in HNSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Though the current standard methods for detection of HPV infection in OPSCC are based on detection of E6/E7 mRNA detection [ 33 ], OPSCC tumor samples were mainly obtained as FFPE tissue in which RNA might not be reliably preserved [ 34 36 ]. Therefore, in our study, we selected HPV DNA detection method by qPCR to confirm the presence of HPV infection in HNSCC.…”
Section: Discussionmentioning
confidence: 99%
“…The fluorescent signal is read in real time at each amplification cycle, generating curves which, compared to a standard, allow for a quantitative evaluation of the viral load. Several studies have shown a statistically valid correlation between viral load and risk of developing cervical cancer and high sensitivity, reproducibility, and speed of execution [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…The determination of the mRNA transcripts of E6/E7 oncoproteins, a useful prognostic indicator of the progression of lesions towards cervicocarcinoma, uses NASBA (nucleic acid sequence-based amplification) technology based on isothermal amplification (conducted at 41°C) of the target RNA and on the use of particular probes defined as molecular beacons capable of emitting fluorescence at two different wavelengths when a complementary sequence is present [ 35 , 45 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Some risk factors have been described, including smoking, alcohol abuse, and human papillomavirus (HPV) infection [ 1 , 2 ]. HPV plays a role in the development of a subset of HNCs and, notably, oropharyngeal cancer (OPC) [ 3 ]. The role of HPV is not so clear in non-oropharyngeal carcinomas (non-OPCs), but some reports suggest a possible association between HPV infection and nasopharyngeal cancers [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…HPV plays a role in the development of a subset of HNCs and, notably, oropharyngeal cancer (OPC) [ 3 ]. The role of HPV is not so clear in non-oropharyngeal carcinomas (non-OPCs), but some reports suggest a possible association between HPV infection and nasopharyngeal cancers [ 3 , 4 , 5 ]. HPV-induced OPC has different biological behavior and a better prognosis compared to non-HPV-induced OPC, and the eighth-edition Tumor-Node-Metastasis (TNM) classification now separates these two types [ 3 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%